,,Offene" und „geschlossene" Transformation:: Von peripheren und noch periphereren Kapitalismen in Osteuropa - Neunhöffer, Gisela; Schüttplez, Anne (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
The article examines different modes of peripheralisation in Eastern Europe in the process of transformation. While in both, the EU candidate countries and in Russia, patterns of peripheral capitalism can be observed, pursued by and in the interest of transnational political and economic interest coalitions, these take different forms. The EU candidate countries undergo a more coherent variant of transformation, structured by the pressures of the accession process and a subordinated integration into European production networks. On the contrary, Russia has seen a much more open and unstructured process of integration into the global economy, expressed so far mainly in capital fiight, export of raw materials and import of vast amount of industrial goods.